Penguatan Pembelajaran Berwawasan Kebangsaan Melalui Metode Insersi Untuk Guru PAUD Di Kabupaten Wonogiri - Ardhana Januar Mahardhani; Betty Yulia Wulansari; Rudi Ruhardi (STMIK Royal, 2022)
Abstract: The existence of the Covid-19 pandemic makes the learning process in early childhood ineffective, including in the delivery of national insight material. The use of online platforms apparently cannot be done in the learning process in Purwantoro District, Wonogiri Regency because many parents do not understand about the operation of online learning, parents who work full time, and geographical conditions that do not support it so that signaling is difficult. This community service activity is carried out in collaboration by the University of Muhammadiyah Ponorogo and the Institute of Kebangsaanic Studies Muhammadiyah Pacitan in collaboration with HIMPAUD, Purwantoro District, Wonogiri Regency. This activity aims to assist teachers in increasing students' understanding of national insight through the insertion method in learning materials. Activities are carried out online with the implementation stages being pre-activity, activity implementation, activity evaluation, and follow-up activities. From the results that have been carried out, it can be concluded that 94% of participants have understood the use of the insertion method in the implementation of learning so that students can understand the national insight in every material presented by the teacherKeywords: insertion; PAUD; national insightsAbstrak: Adanya pandemi Covid-19 menjadikan proses pembelajaran pada anak usia dini tidak efektif, termasuk dalam penyampaian materi wawasan kebangsaan. Penggunaan platform online ternyata tidak bisa dilakukan pada proses pembelajaran di kecamatan Purwantoro kabupaten Wonogiri karena banyak orang tua yang belum paham tentang pengoperasionalan pembelajaran online, orang tua yang bekerja secara fulltime, serta kondisi geografis yang tidak mendukung sehingga sulitnya sinyal. Kegiatan pengabdian kepada masyarakat ini dilaksanakan secara kolaborasi oleh Universitas Muhammadiyah Ponorogo dan Institut Kebangsaan Studies Muhammadiyah Pacitan bekerjasama dengan HIMPAUD kecamatan Purwantoro kabupaten Wonogiri. Kegiatan ini bertujuan untuk membantu guru dalam meningkatkan pemahaman siswa tentang wawasan kebangsaan melalui metode insersi dalam materi pembelajaran. Kegiatan dilaksanakan melalui dalam jaringan (online) dengan tahap pelaksanaan adalah pra kegiatan, pelaksanaan kegiatan, evaluasi kegiatan, dan tindak lanjut kegiatan. Dari hasil yang telah dilaksanakan diperoleh hasil bahwa 94% peserta telah paham tentang penggunaan metode insersi dalam pelaksanaan pembelajaran sehingga siswa dapat memahami tentang wawasan kebangsaan dalam setiap materi yang disampaikan oleh guru.Kata kunci: insersi; PAUD; wawasan kebangsaan